The Process of Distributing Grants to Farmers and Ranchers in Badung Regency - I Kadek Surya Dwi Merta; Gede Mekse Korri Arisena; I Dewa Ayu Sri Yudhari (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
Grants are one form of government assistance aimed at supporting research, improving social welfare, economic development, education, and technological innovation for the community. Badung Regency has very high potential in regional development and is planning to improve the welfare of its people. With the highest local revenue in Bali Province, Badung Regency has become the fastest growing regency. In providing grant assistance, there are several requirements and types of grants that can be submitted using an institutional account by the community. Usually, there are obstacles in the submission process, related to the difference between the number of submissions and those accepted. Badung Regency developed the website e-hibah.badungkab.go.id to improve the efficiency and effectiveness of management so that obstacles can be overcome quickly. A literature review method was used in this study to discuss in detail the stages involved in the e-hibah.badungkab.go.id website regarding grant distribution. Grant distribution in Badung Regency through the e-hibah.badungkab.go.id website provides information on grant applications through three stages, namely: 1. Grant Proposal Submission, 2. Grant Proposal Evaluation, 3. Grant Disbursement. These three stages are contained in the Badung Regent Regulation concerning the distribution of grant funds in Badung Regency. The use of an online platform demonstrates the government's commitment to utilizing technology to simplify and speed up submitting and verifying grant proposals.